How can tourist experience and perceive authenticity impact behavioral intentions and perceived value by tourist? - Afonso, Ana Filipa do Amparo Leitão (2019)
Playing a major role in the Portuguese economy, tourism is not only a relevant segment for Portugal but also for the city of Lisbon, being Lisbon’s the major export sector. In the life of “alfacinhas” (name called to people from Lisbon), tourism represents more than an economical tool, it’s a booster of construction, rehabilitation, culture activities, attraction of national and international events, business deals, students and even new residents. Lisbon’s weather, cuisine and uniqueness are just some of the features that attract and spark interest in its potential future/previous visitors. Focusing on tourism marketing, the main objectives of this dissertation are to understand how the perception of the destination’s authenticity and the experience lived during the visit, by the tourist, can influence and determine tourists’ emotional states and how these emotional states can impact the behavioral intentions, after the visit, and the Lisbon’s perceive value. This thematic proves important, both from a theoretical and practical viewpoint since tourism, nowadays, is a trend topic and brings so many benefits for the city of Lisbon and to Portugal, in a global way. In order to raise future tourists and the level of satisfaction of the current ones, this dissertation is relevant for the marketing standpoint to realize what to improve and how to improve it.